(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Corrosion in pipelines is one of the serious challenges in the field of mechanical engineering, particularly with regards to oil and gas, water distribution, and other chemical processes. This article addresses an in-depth effect of corrosion mechanisms, factors influencing corrosion rates, and the effect of corrosion on pipeline integrity. Additionally, the paper will explore advanced methods for detecting, preventing, and mitigating corrosion in pipelines. The study is supported by real-world case studies illustrating the consequences of pipeline failures due to corrosion and emphasizes the importance of regular maintenance and innovative material selection. The findings are intended to guide mechanical engineers in designing more durable and corrosion-resistant pipeline systems. This comprehensive study examines corrosion mechanisms, factors influencing corrosion rates, and advanced methods for detecting, preventing, and mitigating corrosion in pipelines, with real-world case studies underscoring the importance of regular maintenance and innovative material selection for mechanical engineers.